A study of human emotional: Review - Nurnadia, M. Khair; Sazali, Yaacob, Prof. Dr.; Muthusamy, Hariharan, Dr.; Shafriza Nisha, Basah, Dr. (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://ieeexplore.ieee.org/